SISTEM INFORMASI DAN BUSINESS PROCESS REENGINEERING - M. D. Rahadhini (Universitas Slamet Riyadi, 2008)
Abstract Today’s environment is characterized by increasing levels of competition. Enterprises wanting to increase their market share or obtain profits must adapt to changes in the environment. Consequently, many changes in business methods are beginning to appear. One of them is Business Process Reengineering (BPR), defined as the fundamental rethinking and radical design of business processes to achieve dramatic improvements in critical, contemporary measures of performance. Among the potential enablers of BPR is Information Technology (IT). IT makes it possible to obtain improvements in BPR, through not just by itself. This paper will demonstrate the importance of IT in one of the most prominent methodologies. Enterprises can make their tasks easier, redesign their organization, change the way they work, and achieve spectacular improvement using, among other enablers, IT. Keywords: information technology, BPR, organizational performance